1997
DOI: 10.1007/s000110050093
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of clodronate and indomethacin in the treatment of adjuvant arthritis

Abstract: Clodronate and indomethacin have fairly similar efficacy in suppressing the intensity of joint swelling and preventing bone lesions in adjuvant arthritic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 21 publications
2
13
0
2
Order By: Relevance
“…In contrast, lower cumulative doses of free clodronate, i. e. 13.5 mg/kg i. v. or 18.2 mg/kg i. p. failed to inhibit inflammation and cartilage destruction and had only a modest suppressive effect on clinical disease activity, even when administered during the early, acute phase of AIA [9,21]. This observation that relatively high doses of free clodronate are necessary to inhibit inflammation and joint destruction in animal models of RA is in accordance with the findings in adjuvant arthritic rats [11,22]. On the other hand, the suppressive effect of clodronate on inflammation and joint destruction is also dependent on the form of administration.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In contrast, lower cumulative doses of free clodronate, i. e. 13.5 mg/kg i. v. or 18.2 mg/kg i. p. failed to inhibit inflammation and cartilage destruction and had only a modest suppressive effect on clinical disease activity, even when administered during the early, acute phase of AIA [9,21]. This observation that relatively high doses of free clodronate are necessary to inhibit inflammation and joint destruction in animal models of RA is in accordance with the findings in adjuvant arthritic rats [11,22]. On the other hand, the suppressive effect of clodronate on inflammation and joint destruction is also dependent on the form of administration.…”
Section: Discussionsupporting
confidence: 77%
“…It has been shown in adjuvant arthritis [11,22,37], collagen-induced arthritis [38] and in AIA [9] that inhibition of periarticular bone resorption can be achieved with clodronate doses lower than those necessary to suppress inflammation and cartilage destruction. In the present study, all three treatment regimens with clodronate inhibited bone resorption and periarticular bone loss.…”
Section: Effects Of Clodronate On Arthritis-associated Periarticular mentioning
confidence: 99%
“…Despite their success in preventing systemic bone loss, however, trials with bisphosphonates in patients with RA have not demonstrated efficacy with respect to attenuating the progression of focal bone erosions (6)(7)(8)(9)(10). In contrast, results of studies in several different animal models of inflammatory arthritis indicate that bisphosphonate treatment can produce beneficial effects in both systemic bone loss and progression of focal bone erosions (3,(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…In inflammation-associated bone disorders, long-term treatment with high doses of free clodronate reduces bone lesions and/or inflammatory signs (28, 40 -42). Treatment of systemic experimental arthritides with clodronate is associated with a decrease in serum osteocalcin (a marker of osteoblast function) and crosslinked telopeptides of type I collagen (a marker of bone resorption); this indicates that the normalization of bone turnover is mediated by inhibition of both bone resorption and bone formation (28,41). The present results are partially at odd with this interpretation, since free clodronate decreased the osteoid-covered surface and the osteoid-covered surface with osteoblasts (in accordance with a direct action on osteoblasts; 43-47), but did not significantly decrease the resorption surface with osteoclasts.…”
Section: Free Clodronatementioning
confidence: 99%